Islamic Ethics and Self-Development: Communitarian, Individualist and Pietistic Perspectives - Belhaj, Abdessamad (Socio Religia, 2024)
Islamic self-help literature is one of the most widely read and widespread literature among Muslims today. However, an in-depth study of Islamic self-help discourse, the producers of this literature, and the context in which it emerged is still very limited. This literature plays an important role in how Islamic ethics is understood and practiced, although its influence has still not been adequately researched. This article seeks to fill this gap by exploring three widely circulated discourses of Islamic self-help, namely the works of al-Hāshimī, Ayad, and al-ʻArīfī. This research aims to: (1) analyze the structure and coherence of these discourses, and (2) understand their role in bridging Islamic ethics with global ethics. The study identifies three main discourses: deontological-communitarian, holistic-individualistic, and global-pietistic, based on the work of three authors who have received international attention, particularly in the West. The results show that Islamic ethics explicitly interact with global ethics, both in theory about the self (autonomy, the search for happiness, harmony of body and mind, pleasure, etc.) and in practice (management, socio-political activities, sports, etc.). These findings underscore the importance of reading Islamic ethics in an ever-evolving modern context. Although based on a limited sample of texts, the study provides relevant preliminary insights to expand the study of Islamic ethics in other areas, such as business and bioethics.